Variable entanglement density constitutive rheological model for polymeric fluids - Stephanou, Pavlos S. (My University, 2024)
A variable-entanglement density constitutive model is developed for the description of the rheological properties of entangled polymer melts and concentrated polymer solutions using non-equilibrium thermodynamics (NET). It proposes two evolution equations: one for the average number of entanglements per chain and one for the orientation of entanglement strands. Direct comparison with non-equilibrium molecular dynamics simulation data shows that the model can accurately describe the loss of entanglements due to the applied flow for three molecular weights by using the same value for the convective constraint release (CCR) parameter. The CCR relaxation time depends on the trace of the inverse of the orientation tensor instead of an explicit dependency on the velocity gradient. Finally, the stress tensor contains an additional contribution inspired by the Curtiss-Bird or tumbling snake model. Overall, the model proposed here carefully derives via NET and builds upon the work of Ianniruberto-Marrucci when stretching is not considered. Graphical abstract: (Figure presented.)
Keywords: Convective constraint release; Differential constitutive equation; Entanglement density; Non-equilibrium thermodynamics; Tube model